The relationship between epicardial adipose tissue and endothelial dysfunction in patients with type 2 diabetes mellitus - Ahmet Çelik; Mustafa Topuz; Yavuz Gözükara; Ahmet Gündeş; Emrah Yeşil; Didem Ovla; İsmail Türkay Özcan (KARE Publishing, 2014)
Objectives: Epicardial adipose tissue (EAT) has been shown to be related to cardiovascular risk. The aim of the present study was to investigate the relationship between EAT and endothelial function in patients with type 2 diabetes mellitus (DM). Study design: Type 2 DM patients were divided into two groups according to their brachial flow-mediated dilatation (FMD) values. The endothelial dysfunction (ED) group consisted of 46 patients with FMD change of <7%, while 46 patients with FMD change of >7% were accepted as the non-ED group. EAT thickness was measured on the right ventricular free wall from the transthoracic echocardiographic parasternal long- and short-axis views. The patients' demographic, anthropometric and laboratory findings were recorded. Results: The mean diameter of EAT was 8.0+-1.8 cm in the ED group and 6.6+-1.2 cm in the non-ED group (p<0.001). The HbA1c levels were significantly higher in the ED group than non-ED group (8.55 [7.30-9.80], 7.45 [6.50-9.30], respectively; p=0.042). There were a negative correlation between FMD values and EAT (r=-0.437, p<0.001). The FMD values were weakly and negatively correlated with DM duration and HbA1c levels (r=-0.216, p=0.038; r=-0.266, p=0.010, respectively). EAT thickness was strongly correlated with body mass index (BMI) and waist length (r=0.405, p<0.001; r=0.515, p<0.001, respectively). The neutrophil count was significantly higher in the ED group than in the non-ED group. In multivariate logistic regression analysis, HbA1c and EAT diameters were found as predictors of ED in type 2 DM (odds ratio (OR): 1.887, 95% confidence interval (CI): 1.298-2.743, p=0.001; OR: 1.485, 95% CI: 1.054-2.093). Conclusion: EAT thickness predicts ED in patients with type 2 DM.